Associations between arterial oxygen saturation, body size and limb measurements among high‐altitude andean children. Issue 5 (1st August 2013) - Pomeroy, Emma; Stock, Jay T.; Stanojevic, Sanja; Miranda, J. Jaime; Cole, Tim J.; Wells, Jonathan C.K.
ABSTRACT Objectives The relative influences of hypoxia and other environmental stressors on growth at altitude remain unclear. Previous work demonstrated an association between peripheral arterial oxygen saturation (SpO2) and anthropometry (especially tibia length) among Tibetan and Han children at altitude. We investigated whether similar associations exist among Andeans, and the patterning of associations between SpO2 and anthropometry. Methods Stature, head‐trunk height, total upper and lower limb lengths, zeugopod (ulna and tibia) and autopod (hand and foot) lengths were measured in Peruvian children (0.5–14 years) living at >3000 m altitude. SpO2 was measured by pulse oximetry. Anthropometry was converted to internal z scores. Correlation and multiple regression were used to examine associations between anthropometry z scores and SpO2, altitude, or SpO2 adjusted for altitude since altitude is a major determinant of variation in SpO2. Results SpO2 and altitude show weak, significant correlations with zeugopod length z scores and still weaker significant correlations with total upper and lower limb length z scores. Correlations with z scores for stature, head‐trunk height, or autopod lengths are not significant. Adjusted for altitude, there is no significant association between anthropometry and SpO2. Conclusions Associations between SpO2 or altitude and total limb and zeugopod length z scores exist among Andean children. However, the relationships are relatively weak, and while the relationship between anthropometry and altitude may be partly mediated by SpO2, other factors that covary with altitude (e.g., socioeconomic status, health) are likely to influence anthropometry. The results support suggestions that zeugopod lengths are particularly sensitive to environmental stressors. Am. J. Hum. Biol., 25:629–636, 2013. © 2013 Wiley Periodicals, Inc.